The Apollon 10 PW laser: experimental and theoretical investigation of the temporal characteristics. (28th September 2016) - Papadopoulos, D.N.; Zou, J.P.; Le Blanc, C.; Chériaux, G.; Georges, P.; Druon, F.; Mennerat, G.; Ramirez, P.; Martin, L.; Fréneaux, A.; Beluze, A.; Lebas, N.; et al.
Abstract : The objective of the Apollon 10 PW project is the generation of 10 PW peak power pulses of 15 fs at $1~\text{shot}~\text{min}^{-1}$ . In this paper a brief update on the current status of the Apollon project is presented, followed by a more detailed presentation of our experimental and theoretical investigations of the temporal characteristics of the laser. More specifically the design considerations as well as the technological and physical limitations to achieve the intended pulse duration and contrast are discussed.